Assessing Impact in Dynamic and Complex Environments: Systemic Action Research and Participatory Systemic Inquiry - and Burns, Danny (IDS, 2014)
This CDI Practice Paper is about the uses of Systemic Action Research (SAR) and Participatory Systemic Inquiry (PSI) for impact assessment (Burns 2006, 2007, 2011, 2012, 2013; Wadsworth 2001, 2010).